Analysis of Calcium, Iron, Ash, Fat, and Water Content in Fresh and Processed Cow's Milk Using Atomic Absorption Spectrophotometry Methods - Amalia, Rizka; Pindona, Zelvia; Rusdiana, Nita; Pratiwi, Dina (Journal of Fundamental and Applied Pharmaceutical Science, 2023)
Milk is a source of nutrition for the body's growth, containing calcium and iron minerals. This study analyzes the optimal calcium, iron, ash, water, and fat levels in fresh and processed cow's milk. This study used five samples: pure milk (S1), pasteurized pure milk (S2), pasteurized milk with sugar (S3), pasteurized milk with paste coloring and citric acid (S4), and pasteurized milk with powder coloring(S5). The results showed that the calcium content of milk 4 (S4) treated with pasteurized milk added with sugar and paste coloring and citric acid had a higher calcium content than the other four samples by 98.61 mg/kg, at levels of milk iron 5 (S5) treated with pasteurized milk added with sugar and powdered dyes had a higher iron content than the other four samples by 73.81 mg/kg. The ash content of pure milk was higher at 0.96%. The fat content of pasteurized milk, the taste of coloring paste and powder, was higher than the other three samples at 2.80%. The water content of pasteurized added sugar milk was higher than the other four samples at 88.58%. Pure milk had the most optimal calcium (Ca) and iron (Fe) levels from the other four samples.